Sintaxi dels clítics pronominals en català medieval - Batllori, Montserrat; Iglésias, Narcís; Martins, Ana Maria (Caplletra. Revista Internacional de Filologia, 2005)
In this article a classical topic of the studies on historical syntax is analysed: the enclitical or proclitical collocation of atonic pronouns in Catalan. From a Romanic and comparative prespective, it is shown that the clitical pronouns in Old Catalan have a very similar behaviour to the atonic ones in other Romanic lenguages such as, for instance, medieval Spanish or Portuguese, on one hand, and French, on the other. Specifically, we analyse phenomena such as: (i) pronoun collocation in connection to the verb in main and subordinate propositions, in propositions where the verb is the main constituent, in negative propositions, (ii) duplication of clitics or (iii) clitic raising.